2020
DOI: 10.1016/j.mmcr.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A case of rhinocerebral mucormycosis with brain abscess drained by endoscopic endonasal skull base surgery

Abstract: A 70-year-old Japanese man undergoing remission induction therapy for acute monocytic leukemia (AML-M5b) developed fever and headache, and was started on antibiotics and liposomal amphotericin B (L-AMB). There was no improvement, and computed tomography and contrast-enhanced magnetic resonance imaging revealed acute rhinosinusitis and brain abscess. Successful endoscopic endonasal surgery was performed at this point, providing drainage for the rhinosinusitis and abscess. Histopathological findings showed the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Uraguchi et al in their study had treated a case of rhinocerebral mucormycosis with brain abscess drained by endoscopic endonasal skull base surgery in a 70-year-old male [9].…”
Section: Discussionmentioning
confidence: 99%
“…Uraguchi et al in their study had treated a case of rhinocerebral mucormycosis with brain abscess drained by endoscopic endonasal skull base surgery in a 70-year-old male [9].…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis infects the nervous system in 20% of hematological cases and brain abscess occurs rarely in 2 of 43 patients with mucormycosis. 5,6 Unfortunately, it has been observed that mucormycosis has been rising since the COVID-19 pandemic began, and recently it has become an issue of concern for our healthcare system. 1 The condition could be a consequence of a dysregulated immune system due to a reduction in T cell count, altered CD4/CD8 ratio, and overuse of immunosuppresses like corticosteroids following the COVID-19 which is exacerbated by uncontrolled blood sugar in people with undetermined diabetes cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis has five different spread sites: rhino‐cerebral, gastrointestinal, cutaneous, respiratory, and disseminated. ROCM is the predominant manifestation of the infection which can progress to the orbital and deeper sites of the brain through paranasal sinuses 1,5 and could result in uncommon presentations such as seizures, reduced LOC, or ophthalmic involvement. Mucormycosis infects the nervous system in 20% of hematological cases and brain abscess occurs rarely in 2 of 43 patients with mucormycosis 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal uid rhinorrhea is rarely documented with such fungal infection in literature. There are only a few case reports of iatrogenic CSF rhinorrhea in ROCM during orbital exenteration and sinus surgery [8,9,10] .…”
Section: Introductionmentioning
confidence: 99%